Croatian Universities Under the Microscope: Who Leads, Who Lags, and Why? - Fotova Cikovic, Katerina; Kecek, Damira; Cvetkoska, Violeta (EURO, 2024)
In an era propelled by knowledge, our study pioneers a cutting-edge evaluation of teaching and research efficiency in Croatian universities, employing a sophisticated blend of AHP, DEA, and regression analysis. Our extensive literature review from the Scopus database, spanning scholarly discourse from inception to 2023, unveiled crucial focuses: teaching and research efficiency, and their convergence. Distilling in sights, we constructed a refined framework for inputs and outputs, utilizing AHP, and engaging diverse respondents—Ministry of Edu cation, university rectors, and higher education policy advisors—in a structured comparison. They assigned relative importance to input and output hierarchies for teaching and research efficiency. The highest-ranked factors, determined by AHP, shaped the DEA analysis, revealing the efficiency frontier and enabling targeted improvement strategies for universities based on quantified efficiency scores. In parallel, our study delves into the assessment of managerial ability within universities, a pivotal yet often overlooked aspect. Adopting methodologies proposed by Demerjian and Lev (2021) and Banker and Park (2021), we measure the efficacy of managerial decision-making in steering institutions toward relative teaching and research efficiency. By identifying determinants of managerial ability, our analysis contributes insights into the leadership dynamics shaping the overall efficiency of Croatian universities.
https://euro2024cph.dk/programme/conference-program